A Novel OTP Based Pin Generation and Face Recognition Methods in Online Banking - M. Krithika Devi,; PL. Baby Shalini,; S. Abirami, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
An integral component of contemporary banking is now internet banking. Due to the present password-based authentication paradigms' inadequacies in terms of efficiency and robustness, as well as their susceptibility to automated assaults, several attempts are successful in gaining access to social network accounts. The easiest solution is to add more identifying features, such one-time PIN numbers produced by the user's own device (like a smartphone) or received via SMS, to the single factor (password-based) authentication procedure. Real-time facial recognition technology is a biometric authentication tool that may be used to increase the security of online banking transactions. With the use of this technology, clients' identities may be instantly and conveniently verified. The goal of this project is to create an online banking system that authenticates customers using real-time facial recognition technology. Customers will be able to do banking tasks including money transfers, bill payments, and balance inquiries using the system's user-friendly and secure interface. A face recognition algorithm, such Grassmann Learning, which can record and evaluate a customer's facial traits in real time, will be included into the system. To confirm the customer's identification, the algorithm will match the customer's facial traits with those in the bank's database. PIN verification at a second level using an OTP basis. Using a challenge keypad, the user will produce the PIN number in this technique. The technology would give users a safe and convenient interface to conduct real-time financial transactions. Notifications about banking interface access and amount transactions are sent to the user in this suggested net-banking application.
Keywords: Framework Creation; User Registration; User Authentication; Face Recognition; OTP based PIN Verification; Account Access